2014
DOI: 10.1108/jgr-03-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

The global public health issue of pharmaceutical waste: what role for pharmacists?

Abstract: Pharmaceuticals have played an important role in improving the quality of life of the human population in modern times. However, it must also be acknowledged that both the production and use of pharmaceuticals have a significant, negative impact on the environment and consequently, a negative impact on the health of humans and wildlife. This negative impact is due to the embedded carbon in pharmaceuticals' manufacture and distribution and the waste generated in their manufacture, consumption and disposal. Phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Although disposal of medications is generally thought of as the discarding of a medicinal product, households may also pass on their previously-stored, unwanted medications to other patients such as friends and family members. Such a practice may be the result of patient non-compliance to therapy, excessive prescribing by physicians, a change in the treatment course, improvement of patient health, or their death [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although disposal of medications is generally thought of as the discarding of a medicinal product, households may also pass on their previously-stored, unwanted medications to other patients such as friends and family members. Such a practice may be the result of patient non-compliance to therapy, excessive prescribing by physicians, a change in the treatment course, improvement of patient health, or their death [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the CSR and corporate sustainability areas in the pharmaceutical industry have focused on various aspects, such as: the relation between engagement in CSR activities and positive financial results (Min, Desmoulins_Lebeaut & Esposito, 2017); challenges of reverse logistics management in the pharmaceutical industry (Luna & Vianna, 2019;Naryana & Elias, 2014); the management of the complex stakeholder network (O'Riodan & Fairbrass, 2008;O´Riodan & Fairbrass, 2014) as well as the issue of the industry's reputation (Fischer, 2009). Moreover, Singleton, Nissen, Barter and McIntosh (2014) in their literarture review cited the three main sources of the pharmaceutical huge negative impact in the enviroment: the carbon footprint of manufacturing and distribution chain; the incineration of unwanted pharmaceuticals, and the direct chemical effects of the pharmaceutical in nature (Kummerer, 2010), and suggested that pharmaceutics should have an action to reduce such impacts. However, no study was found in the literature which investigated barter in the pharmaceutical industry's sustainability.…”
Section: Sustainable Development and The Triple Bottom Linementioning
confidence: 99%
“…An estimated GBP 300 million worth of prescribed medicines are wasted ever year in the UK alone, and similar situations are reported in other countries [1,2]. Medication non-adherence and many other causes, such as over prescribing, over ordering, change of treatment, or a patient dying, create unused and unexpired prescribed medicines which cannot be returned to pharmacies for re-dispensing due to government policies [3].…”
Section: Introductionmentioning
confidence: 99%